Electromyographic characteristic of dancer motions depending on dancer sex and sport qualification - Yu. P. Bredikhina; A. V. Tikhonova; Ye. V. Putintseva; L. V. Kapilevich (Бюллетень сибирской медицины, 2012)
The period of electric activity of muscles is shortened in the group of high-qualification dancers. This is obviously connected with the shorter time needed to perform a motion, because the synchronization of motor fibers (by the mean frequency) increases and, as a result, the period of electric activity decreases. Consequently, just the character of bioelectric indices of rectus muscles of thigh determines the level of special motor fitness in sport dances: the higher is the dancer skill level, the more pronounced in the difference in the amplitudes and mean frequency of second realization.